2021
DOI: 10.1038/s43018-021-00194-9
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil oxidative stress mediates obesity-associated vascular dysfunction and metastatic transmigration

Abstract: Obesity enhances BC extravasation by modifying the endothelium. To investigate the effects of obesity on cancer extravasation, we used a syngeneic BC cell line derived from the C57BL6 mouse mammary tumor virus-polyoma middle T antigen (MMTV-PyMT) model combined with a diet-induced obesity (DIO) model. Wild type (WT) C57BL6 female mice were enrolled on a low-fat (LF) (10% kcal) or high-fat (HF) (60% kcal) diet for 15 weeks (Fig. 1a,b) 10 , followed by tail vein injection of fluorescently labeled BC cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 83 publications
1
38
0
Order By: Relevance
“…Early studies have shown that cancer-induced NETs act largely within the circulation, where they facilitate cancer-associated thrombosis ( Demers et al, 2012 ; Hell et al, 2016 ; Thalin et al, 2016 ; Thomas et al, 2015 ) and sequester circulating tumor cells to escort metastases ( Cools-Lartigue et al, 2013 ). Subsequent studies revealed that NETs affect essentially every step of the metastatic cascade, including primary tumor progression ( Guglietta et al, 2016 ), invasion and migration ( Park et al, 2016 ), survival in the circulation ( Spiegel et al, 2016 ; Szczerba et al, 2019 ; Teijeira et al, 2020 ), chemotaxis to secondary niches ( Yang et al, 2020 ), extravasation ( McDowell et al, 2021 ; Spiegel et al, 2016 ), metastatic colonization ( Wculek and Malanchi, 2015 ; Yang et al, 2020 ), and outgrowth of metastatic tumor cells ( Albrengues et al, 2018 ; Xiao et al, 2021 ). However, a remaining knowledge gap is how tumors trigger NETosis—Is this a direct consequence of tumor-derived factors?…”
Section: The Unheeded Complexity Of Neutrophil Heterogeneity In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies have shown that cancer-induced NETs act largely within the circulation, where they facilitate cancer-associated thrombosis ( Demers et al, 2012 ; Hell et al, 2016 ; Thalin et al, 2016 ; Thomas et al, 2015 ) and sequester circulating tumor cells to escort metastases ( Cools-Lartigue et al, 2013 ). Subsequent studies revealed that NETs affect essentially every step of the metastatic cascade, including primary tumor progression ( Guglietta et al, 2016 ), invasion and migration ( Park et al, 2016 ), survival in the circulation ( Spiegel et al, 2016 ; Szczerba et al, 2019 ; Teijeira et al, 2020 ), chemotaxis to secondary niches ( Yang et al, 2020 ), extravasation ( McDowell et al, 2021 ; Spiegel et al, 2016 ), metastatic colonization ( Wculek and Malanchi, 2015 ; Yang et al, 2020 ), and outgrowth of metastatic tumor cells ( Albrengues et al, 2018 ; Xiao et al, 2021 ). However, a remaining knowledge gap is how tumors trigger NETosis—Is this a direct consequence of tumor-derived factors?…”
Section: The Unheeded Complexity Of Neutrophil Heterogeneity In Cancermentioning
confidence: 99%
“…In the non-tumor bearing setting, obesity stimulates myelopoiesis to yield elevated neutrophils and Gr1 + cells in multiple organs ( Nagareddy et al, 2014 ; Xia et al, 2011 ). Lung neutrophils from obese and lean mice have a highly divergent transcriptome, with a significant enrichment in pathways related to oxidative stress in obese hosts coinciding with enhanced NETosis ( McDowell et al, 2021 ). In cancer, both genetic- and diet-induced obesity models have elevated peripheral and pulmonary neutrophils that promote breast cancer metastasis to the lung in a GM-CSF–dependent manner ( McDowell et al, 2021 ; Quail et al, 2017 ).…”
Section: The Unheeded Complexity Of Neutrophil Heterogeneity In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In higher animals, the presence of cells with oxidative killing (e.g. neutrophils) can lead to tissue damage [51,67]. Given this oxidative stress, and the origin of the clock as an oxidative stress buffer, circadian modulation of innate immunity has been proposed and studied, in animals.…”
Section: Introductionmentioning
confidence: 99%
“…More recent data indicate that NETs can directly eliminate melanoma cells, suggesting a tumor-suppressive effect ( 20 ). Recent studies investigating the impact of NETs on breast cancer cell dissemination indicate that NET release (also termed “NETosis”) is associated with trapping and extravasation of blood circulating cancer cells ( 21 ). It was also reported that NETs are able to enhance the motility of breast cancer cells, promoting their recruitment into premetastatic livers ( 22 ).…”
mentioning
confidence: 99%